Oculomotor Assessment in Children - Doettl, Steven M.; McCaslin, Devin L. (Seminars in Hearing, 2018)
Oculomotor evaluation as part of videonystagmography is an integral tool in the assessment of vestibular function providing a global assessment of the neurological pathways associated with oculomotor function. The value of an oculomotor evaluation for pediatric evaluation is well established; however, many questions can also arise with the application to the pediatric population. Oculomotor function is age dependent which can have a significant effect on the test results obtain in children. The underlying neural substrates and age effects are discussed across the literature with specific results from recent research using clinical oculomotor equipment and protocols. The evidence suggests there are several key differences in the pediatric population compared with adults. These include longer saccade latencies, reduced smooth pursuit gain, increased optokinetic asymmetry, increased variability in all responses, and increased artifact in saccade and smooth pursuit testing.
Keywords: Children; dizziness; videonystagmography; oculomotor